Identification of Fungal Infections on the Fingernails of Warteg Employees in Pekalongan Regency - Laela Rizqi Fitriani; Agus Riyanto (INDOGENIUS, 2026)
Background & Objective: Fungi are one of the microorganisms that cause disease in humans. Fungi are cosmopolitan organisms that grow anywhere, including in the air, soil, water, clothing, and even on the human body itself. Fungi can cause quite severe diseases in humans. Most skin and nail infections are the result of a group of homogeneous keratinophilic fungi known as dermatophytes. Dermatophytosis of the fingernails and toenails, unlike dermatophytosis in other parts of the body, is very difficult to treat with medical treatment. This study aims to determine the presence of Dermatophyta and Non-Dermatophyta fungi on the fingernails of warteg employees in Pekalongan Regency. Method: This study is a descriptive study using total sampling with 30 respondents. Result: Examination of 30 fingernail samples from food stall employees yielded positive results for Trichopyton sp. dermatophyte fungi in approximately 17% (5 samples), positive results for Candida sp. non-dermatophyte fungi in 87% (26 samples), and positive results for Aspergillus sp. fungi in 60% (18 samples). Conclusion: Usually, some warteg sellers are found to lack hygiene in their fingernails while working. Risk factors that can cause fungal infections in fingernails in this study include several habits at work, such as frequent direct contact with water, causing the hands to become moist, not many people wearing gloves while working, and not maintaining fingernail hygiene, such as cutting nails more than once every two weeks.